2007
DOI: 10.1002/smll.200600716
|View full text |Cite
|
Sign up to set email alerts
|

Desktop Growth of Carbon‐Nanotube Monoliths with In Situ Optical Imaging

Abstract: Fruits of the forest: A desktop reactor rapidly grows forests of aligned carbon nanotubes (CNTs) to heights of many millimeters by atmospheric‐pressure chemical vapor deposition (see picture). This low‐cost apparatus achieves the reaction temperature by resistive heating of a suspended silicon platform, and achieves a 20‐fold increase in CNT growth rate by thermal pretreatment of the reactant mixture. The film thickness is monitored in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 32 publications
(29 reference statements)
1
37
0
Order By: Relevance
“…Cracking of continuous nanotube forests has been previously observed by in situ optical imaging [24]. Here, up until t = 180 s the forest, grown at T = 720…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Cracking of continuous nanotube forests has been previously observed by in situ optical imaging [24]. Here, up until t = 180 s the forest, grown at T = 720…”
Section: Resultsmentioning
confidence: 67%
“…Several reports demonstrate that nanotube forests grow at an initially rapid rate which drops off either gradually [7,20,21] or suddenly [15,22,23]. Because nanotube forests are attached to a substrate and grown in such abundance, process monitoring can be as simple as making in situ videos of forest growth [4,21,22,24,25]. Due to the large number of nanotubes in close proximity within forests, mechanical stresses induced by interactions between nanotubes are very important factors contributing to their growth [10,18,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…[221] In the growth of aligned CNTs, the CNTs have similar lengths, and it is easy to design in situ methods to monitor the kinetics of aligned CNT growth. [222,223] The growth mark method was used to record the growth rate of aligned CNTs by adding marks during the growth process. [224] It was found that the growth rate was higher in the initial stage and then reached a constant value when the growth temperature was 953 K. Along with increasing C 2 H 2 partial pressure, the axial growth rates also increased, which indicated that the reaction cannot be zero-order in C 2 H 2 .…”
Section: Kinetics Of Cnt Growthmentioning
confidence: 99%
“…By decoupling these processes using two heating zones, one can achieve better control over the growth in terms of forest height. 19 For a typical growth, the first heating zone was heated to 850…”
Section: Appendix A: Carbon Nanotube Forest Growthmentioning
confidence: 99%